Military Translation and its Challenges - Rohach, Oksana; Tyvodar, Andriy; Lelliott, Yulia (My University, 2024)
Military translation is one of the most challenging types of rendering meaning and sense from a source language into a target one. Military texts are characterized by a high level of formality, little emotional colouring, great number of terms, and abbreviations and acronyms. The main methods of translating military terms are direct translation, translation equivalents, description, transliteration, transcription, hybrid translation, and borrowings.
Keywords: military translation; translation methods; accuracy; formality; context sensitivitynges of translation; 81:001.8